How Hand Osteoarthritis, Comorbidity, and Pain Interact to Determine Functional Limitation in Older People: Observations From the European Project on OSteoArthritis Study. Issue 11 (27th October 2016) - Siviero, Paola; Zambon, Sabina; Limongi, Federica; Castell, Maria Victoria; Cooper, Cyrus; Deeg, Dorly J. H.; Denkinger, Michael D.; Dennison, Elaine M.; Edwards, Mark H.; Gesmundo, Antonella; Otero, Ángel; Pedersen, Nancy L.; et al.
Abstract : Objective: To examine the role of comorbidity and pain in the associations of hand osteoarthritis (OA) with self‐reported and performance‐based physical function in a general population of elderly persons. Methods: We studied data from 2, 942 participants ages 65–85 years in the European Project on OSteoArthritis, a collaborative observational study of 6 European cohorts (from Germany, Italy, The Netherlands, Spain, Sweden, and the UK). Outcome measures included self‐reported physical function of the hands measured by the AUStralian/CANadian Osteoarthritis Hand Index (AUSCAN) for hand OA physical function subscale and performance‐based grip strength measured using a strain gauge dynamometer. Results: Comorbidity was not a confounder in the association of hand OA with self‐reported and performance‐based functional limitations, while the role of pain as a mediator was confirmed. Anxiety, depression, stroke, and osteoporosis were associated with AUSCAN scores reflecting more impairment. Depression and osteoporosis were associated with less grip strength. Conclusion: Although comorbidity was decidedly and independently associated with hand functional limitation, it had no effect on the relationship of hand OA with physical function. Hand OA was found to be associated with both self‐reported and performance‐based physical function impairment; the association was found to be partially mediated by pain, which reduced its impact.